Cooperative and Antagonistic Networks: Multidimensional Affinity and Intervention in Ongoing Conflicts, 1946–20011. Issue 2 (16th November 2012) - Corbetta, Renato
Abstract : Corbetta, Renato. (2012) Cooperative and Antagonistic Networks: Multidimensional Affinity and Intervention in Ongoing Conflicts, 1946–2001. International Studies Quarterly, doi: 10.1111/isqu.12020 © 2012 International Studies Association In recent years (social) network approaches have been gaining ground in the field of international relations. Networks between states effectively explain patterns of international conflict and cooperation. One issue where conflict and cooperation converge—and where network analysis finds fruitful application—is the issue of third‐party states' intervention in conflicts. This study investigates whether, and how, conflict expands in the international social space through the cooperative and antagonistic networks generated by states' supportive and oppositional interventions in international disputes. The study adopts a sociological theory of social units' interaction in the social space as a function of their multidimensional affinity to investigate further how such networks form. The hypotheses derived from this theoretical framework are tested using data on third‐party non‐neutral intervention in post‐World War II militarized interstate disputes fromCorbetta and Dixon (2005) . Proximity in the international social space effectively predicts the creation of cooperative ties (supportive interventions) between states, while social distance predicts antagonistic ties (oppositional interventions).